Model Problem Based Learning dalam Meningkatkan Prestasi Belajar Bahasa Indonesia Materi “Menyampaikan Pidato Persuasif” Kelas IX-F Madrasah Tsanawiyah Negeri 2 Kudus pada Semester Gasal Tahun Pelajaran 2019/2020: in the Odd Semester of Academic Year 2019/2020 - Haryanto Haryanto; Wiwik Indarto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhhammadiyah kendari, 2020)
This research aims to describe the Problem Based Learning (PBL) Model in order to improve the Indonesian language learning achievement of class IX-F students at Madrasah Tsanawiyah Negeri 2 Kudus in the Odd Semester of the 2019/2020 Academic Year. The subjects of this classroom action research were students of class IX-F. The research variables consisted of student variables and teacher variables. The research was conducted in two cycles and each cycle consisted of four stages, namely: planning, implementing, observing, and reflecting. The results showed that there was an increase in student achievement in class IX-F. The increase was indicated by (1) the average student achievement in cycle I was 7.08 and cycle II was 8.68; (2) completeness of student learning in the first cycle of 15 students or 50.00% and 15 students or 50.00% who did not complete; and (3) completeness of classical learning in the first cycle was 50.00% and in the second cycle it reached 100.00%. The competency evaluation result of cycle II is better than cycle I which reached the completeness indicator. There is an increase in student activity during the learning process individually or in groups. The student response reached 82.83% as high category.